Holy cows or cash cows? - Orazio Attanasio; Britta Augsburg (Institute for Fiscal Studies (IFS), 2014)
In a recent paper, Anagol, Etang and Karlan (2013) consider the income generated by these owning a cow or a buffalo in two districts of Uttar Pradesh, India. The net profit generated ignoring labour costs, gives rise to a small positive rate of return. Once any reasonable estimate of labour costs is added to costs, the rate of return is a large negative number. The authors conclude that households holding this type of assets do not behave according to the tenets of capitalism. A variety of explanations, typically appealing to religious or cultural factors have been invoked for such a puzzling fact. In this note, we point to a simple explanation that is fully consistent with rational behaviour on the part of Indian farmers. In computing the return on cows and buffaloes, the authors used data from a single year. Cows are assets whose return varies through time. In drought years, when fodder is scarce and expensive, milk production is lower and profits are low. In non-drought years, when fodder is abundant and cheaper, milk production is higher and profits can be considerably higher. The return on cows and buffaloes, like that of many stocks traded on Wall Street, is positive in some years and negative in others. We report evidence from three years of data on the return on cows and buffaloes in the district of Anantapur and show that in one of the three years returns are very high, while in drought years they are similar to the figures obtained by Anagol, Etang and Karlan (2013).
Keywords: 330; Tierhaltung; Ländlicher Raum; Rendite; Lohn; Haushaltsökonomik; Indien